ANALYZING FACTORS OF DIVIDEND POLICY ILLUSTRATED BY COMPANIES OF NASDAQ 100 INDEX - Eugene O. Savchenko; Anna A. Moskaleva (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
From the point of view of getting profits dividend policy is an important factor for investors. It is analyzed regularly, however it is  mainly fragmented and does not show changed taking place. As for  companies of technological sector earlier theoretical provisions  concerning dividend policy need certain corrections. The article  provides an empirical testing (based on regressive analysis) of the  link between the level of company maturity and the size o dividends paid by it, which is one of the key provisions of G. & L.  DeAngelo theory. It is pointed out that these conclusions did not  prove the idea of using indexes identified by G. & L. DeAngelo to  explain dividend policy. The authors put forward a new model of  analysis of factors, the main of them is the indicator of the company  net profit for the year previous to the year of paying dividends.